1992
DOI: 10.1111/j.1365-2273.1992.tb01004.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of middle ear disease in the adult British population

Abstract: The UK National Study of Hearing set out to ascertain the prevalence of hearing impairments of various magnitudes, the prevalence of ear disease and the associated risk factors, and to estimate the percentage of individuals requiring some form of management. A stratified sample of 2708 British adults, aged 18-80 years, was chosen from a sample of 48,313 adults, randomly selected from the electoral roll, for a full otological and audiological assessment. This paper deals primarily with the middle ear results. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
138
1
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 7 publications
7
138
1
5
Order By: Relevance
“…25 Bacteria can get into the ME via the external auditory canal through a perforated TM or following a persistent upper respiratory infection with insufflations of microbial agent via the pharyngeal part of the ET. 24 In our study, patients presented with combinations of symptoms. Almost all the COM patients had complaints of otorrhoea (92.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Bacteria can get into the ME via the external auditory canal through a perforated TM or following a persistent upper respiratory infection with insufflations of microbial agent via the pharyngeal part of the ET. 24 In our study, patients presented with combinations of symptoms. Almost all the COM patients had complaints of otorrhoea (92.5%).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] While a national study on hearing in the United Kingdom found no gender difference. 24 Many investigators have revealed the role of upper respiratory tract abnormalities as causative factors for ET obstruction in the etiopathogenesis of COM. This study evaluated the relationship between COM and sinonasal abnormalities and demonstrates the vital role of diagnostic nasal endoscopy in the objective assessment and definitive management of COM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a robust study, Little et al 4 calculated that 7.4 per cent of the Nepalese population had tympanic membrane pathology, comparing unfavourably with an estimated UK prevalence of chronic otitis media of 4.1 per cent. 6 Interestingly, Little's group found a very similar rate of cholesteatomatous disease (24 per cent) to that seen in our study, and a similar value In addition, we must acknowledge the risk of confounding factors in our study, due to the nature of the ear camps from which our data were drawn. Although there are very limited medical services (and particularly otological services) in the regions visited, there may have been a small proportion of relatively wealthy patients with ear disease who were able to access treatment by other means.…”
Section: Discussionmentioning
confidence: 51%
“…It is well recognised that the condition is a disease of poverty most often found among socially deprived groups within a genetically homogeneous population. 6 It has also been observed that deprived ethnic minorities often demonstrate high rates of chronic ear disease in general. It has been noted, for example, that New Zealand Maoris, Inuit peoples, native Americans and Australian Aboriginals all have high rates of chronic ear disease relative to the more affluent (and genetically distinct) dominant populations of their respective countries.…”
Section: Discussionmentioning
confidence: 99%
“…(6) A perforated tympanic membrane results in loss of hearing due to decreased drum area and liability to recurrent infection of the middle ear mucosa. (9) These problems limit the patient's participation in water sports and for job recruitment in the military service and as a motor vehicle driver. (10) MATERIALS AND METHODS 1.…”
Section: Introductionmentioning
confidence: 99%